Therapeutic hypothermia in infants with hypoxic–ischemic encephalopathy and reversible persistent pulmonary hypertension: short-term hospital outcomes. (2nd December 2018) - Yum, Sook Kyung; Seo, Yu Mi; Kwun, Yoojin; Moon, Cheong-Jun; Youn, Young-Ah; Sung, In Kyung
Abstract: Aim: Neonatal hypoxic ischemic encephalopathy (HIE) patients are at times accompanied by persistent pulmonary hypertension (PPHN), which is by itself another risk factor of adverse outcomes. We aimed to assess the outcome of therapeutic hypothermia (TH) in these patients whom we managed to reverse the shunt flow, as they are expected to be at much higher risk of adverse neurodevelopmental outcome. Methods: We reviewed the medical records of 116 HIE infants (13 with PPHN and 103 without PPHN) who underwent TH between 2012 and 2016. We analyzed the short-term hospital outcomes and brain study results (electroencephalogram and magnetic resonance imaging) of TH in these patients. Results: While infants with PPHN were significantly more likely to be outborn or have meconium aspiration syndrome, and required a longer duration of inotrope and intensive care support, electroencephalographic and brain magnetic resonance findings did not significantly differ according to PPHN status. Conclusion: Based on our study, the hospital outcomes of infants with HIE accompanied by reversible PPHN who underwent TH were in general not significantly graver than those not accompanied by PPHN. Our results suggest that undergoing TH may be more beneficial in HIE infants with PPHN and the risks for possible adverse effects may not be as so high.